PENGGUNAAN IMPLAN PADA ZIGOMA UNTUK REHABILITASI PASCA MASILEKTOMI SEBAGIAN: ZYGOMA IMPLANT-SUPPORTED PROSTHETIC REHABILITATION AFTER PARTIAL MAXILLECTOMY - Eddy Anwar Ketaren; Nelly (TALENTA, 2010)
Patients with severe maxillary defects have major difficulties to re-establish their mastication, speaking, soft tissueprojection and social intergration. The reconstruction of maxilla defect after tumor resection continues to pose a challengefor the reconstructive oral and maxillofacial surgeon. The zygomatic implant, which was introduced in recent years, canoffer a valuable alternative to extensive augmentation procedures. The zygomatic implant represents such a developmentand is inadequate alveolar bone for placing sufficient dental implants. The goal of using the zygoma as an implantanchoring site was to provide predictable posterior anchorage for restoring dentist’s prosthetic efforts. As conclusion,zygoma implant decrease defect, increase maintainance, reconstruct maxilla caused of tumor resection or trauma, wherethe main aims is to return the effort of abturator prosthetic procedure.